Kerinci in Visual Frames: Designing Tourism Identity through Graphic Design - Rizky Alfadly; Dian Fitriani Sari (Judikatif: Jurnal Desain Komunikasi Kreatif, 2025)
Kerinci Regency in Jambi Province has rich natural and cultural potential, but its tourism image and management remain suboptimal. This study demonstrates that a social campaign based on graphic design can serve as an effective educational tool to raise public awareness of smart tourism. Using educational posters, Incung-based ambient media, infographics, and website interface design, educational messages highlight that tourism is not only for recreation but also a learning experience, delivered attractively, communicatively, and consistently with visual art principles. The study also emphasizes the integration of local cultural elements into media design, such as interactive and educational use of the Incung script. The combination of persuasive communication strategies, consistent visual selection, readable typography, and relevant narratives is expected not only to strengthen Kerinci’s tourism visual identity but also to encourage engagement from the community and visitors. By applying a creative concept developed through field observations (5W+1H method), SWOT analysis, the A.I.D.A. model, and market segmentation, the campaign aims to increase the destination’s visibility, improve its image, and support sustainable tourism development. This integrated approach highlights how visual and cultural strategies can enhance both public education and the overall attractiveness of Kerinci as a unique tourist destination.